The Influence of Holistic Health Services by Posyandu Cadres in Increasing Aspects of Mothers' Knowledge Regarding Optimal Baby Care at Posyandu Rajawali, Maniis Village, Maniis District, Purwakarta Regency, Indonesia - Nurhayati, Nurhayati (HM Publisher, 2024)
Holistic health services are health services that include physical, mental, social and spiritual aspects. This service can be provided by posyandu cadres through posyandu activities, such as counseling, counseling and health checks. The aim of this research is to determine the effect of holistic health services by posyandu cadres in increasing aspects of maternal knowledge regarding optimal care for babies at Posyandu Rajawali, Maniis Village, Maniis District, Purwakarta Regency, Indonesia. This research uses quantitative methods with a pre-post test research design with control group. The research population was mothers who had babies aged 0-6 months at Posyandu Rajawali. The research sample consisted of 60 mothers, with 30 mothers as the experimental group and 30 mothers as the control group. The experimental group received holistic health services for 6 months, while the control group did not receive holistic health services. Maternal knowledge was measured before and after the intervention. The results showed that there was a significant difference between the knowledge of mothers in the experimental group and the control group after the intervention (p < 0.05). The knowledge of mothers in the experimental group increased by 15.8%, while the knowledge of mothers in the control group increased by 5.3%. Based on the results of this research, it can be concluded that holistic health services by posyandu cadres can increase aspects of maternal knowledge regarding optimal baby care.